2012
DOI: 10.1016/s1674-8301(12)60016-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of intestinal parasitic infections in certified food-handlers working in food establishments in the City of Nairobi, Kenya

Abstract: Most intestinal parasites are cosmopolitan with the highest prevalence in the tropics and subtopics. Rural-to-urban migration rapidly increases the number of food eating places in towns and their environs. Some of these eating estabishments have poor sanitation and are overcrowded, facilitating disease transmission, especially through food-handling. Our investigations in Nairobi, therefore, were set to determine the presence of intestinal parasites in food-handlers with valid medical certificates. Direct and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 14 publications
3
28
2
Order By: Relevance
“…Even though, there is an operational regulation concerning safety and ensuring minimum quality standards as regards food vendors in public schools, previous studies have shown that food vendors still exhibit quite a number of health hazards in Nigeria [26] and also constitute very significant sources of food contamination especially to school children [27]. The possibility of a sustained contamination with intestinal parasites in food handlers despite medical certification [28] reiterates the urgency and need for Federal Government taking up the sole responsibility for the provision of midday meals to students in schools as stipulated in the National School Health Policy. Furthermore, in this study, students' consumption of midday meals in open places in majority of schools raises very important sanitation and health concerns; it was only in few schools that dining rooms were made available.…”
Section: Discussionmentioning
confidence: 99%
“…Even though, there is an operational regulation concerning safety and ensuring minimum quality standards as regards food vendors in public schools, previous studies have shown that food vendors still exhibit quite a number of health hazards in Nigeria [26] and also constitute very significant sources of food contamination especially to school children [27]. The possibility of a sustained contamination with intestinal parasites in food handlers despite medical certification [28] reiterates the urgency and need for Federal Government taking up the sole responsibility for the provision of midday meals to students in schools as stipulated in the National School Health Policy. Furthermore, in this study, students' consumption of midday meals in open places in majority of schools raises very important sanitation and health concerns; it was only in few schools that dining rooms were made available.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, KwaZulu-Natal (KZN), a province of South Africa, has a significant proportion of the population living in environments where there is lack of adequate sanitation (22.7%) and safe water supplies (15.8%) [13]. In these areas, the standard of living is generally poor and intestinal helminth infections are highly prevalent [14]. Prevalence of intestinal helminths was found to range among adults from 11.2% in the inland region, 30.3% in the north coast region, and 29.2% in the south coast region [15].…”
Section: Introductionmentioning
confidence: 99%
“…This finding was much lower than a finding in Jimma [17] and Bahir Dar [18] in which intestinal parasitic prevalence among food handlers were 45.5% and 41.1%, respectively. This might be due to high intestinal parasitic prevalence in the general population of Jimma and Bahir Dar town [19,20].…”
Section: Discussionmentioning
confidence: 99%